Lack of mutation at codon 531 of SRC in advanced colorectal cancers from Italian patients - Laghi, L (Nature Publishing Group, 2001)
A truncating mutation (C to T transition) at codon 531 of the human protooncogene c-src, possibly accounting for the activation of c-src tyrosine kinase, has been recently identified in a subset of advanced colorectal cancer from North-American patients. However, two subsequent studies have failed to confirm the occurrence of SRC 531 mutation in colorectal cancers from North-European and Asiatic patients, raising the hypothesis that the genetic activation of src in colon cancer might be restricted to patients belonging to specific ethnic groups. We investigated a large series of colorectal cancers from Italian patients (155 cases) with a high prevalence of liver metastasis (43%). Using a PCR-RFLP assay, the occurrence of a SRC 531 mutation was ruled out in all the investigated specimens of primary tumours and/or metastases. Our results demonstrate that SRC Gln531AMB plays no role in the development or in the progression of colorectal cancer among Italian patients. © 2001 Cancer Research Campaign http://www.bjcancer.com